Trade & Investment Perspectives (African Journal of Public Administration & Management, 2026)
African countries will pay close to $89 billion in debt servicing. More than half of the continent’s 1.3 billion people live in countries that spend more on interest payments than they do on education or health, according to the United Nations Trade and Development Agency (UNCTAD).Every year, $88.6 billion leaves Africa in the form of illicit financial flows. Current Debt levels in 20 countries are unsustainable.“Debt has become a silent famine.”— Former Ethiopian Prime Minister Hailemariam Dessalegn. “Investing in Africa’s productivity is therefore not an act of charity; it is a strategy for global stability. The war in Ukraine exposed the fragility of supply chains: when Black Sea grain exports stopped, wheat prices surged 70% and food inflation spread worldwide,” he adds. “Food insecurity anywhere now drives inflation, migration and political unrest everywhere.” source: Devex.New ‘America First’ global health strategy in Africa — one that will work to position American companies to lead in African markets and position African governments as paying customers.
Keywords: Trade; Investment Perspectives